Providing Patient-centered Perinatal Care for Transgender Men and Gender-diverse Individuals: A Collaborative Multidisciplinary Team Approach. Issue 2 (June 2020) - Hahn, M.; Sheran, N.; Weber, S.; Cohan, D.; Obedin-Maliver, J.
Abstract : ( Obstet Gynecol . 2019;134:959–963) Over the course of the last decade, the experience of pregnancy in transgender men (and other gender-diverse people who were assigned female sex at birth) has secured higher visibility within medical journals. While some gender-affirming treatments eliminate fertility, such as hysterectomy or oophorectomy, some transgender men may retain or even desire reproductive capability. Both intended and unintended pregnancies after undergoing gender-affirming processes have occurred, and some transgender men aspire for subsequent pregnancy and parenthood depending on their stage of transition and age. As there is little clinical guidance for medical care from prenatal to postpartum, this is a divulsion of a case intended to help create a more equitable and inclusive health care experience for transgender men and to assure patient-centered care.